Pomegranate seeds: a comprehensive review of traditional uses, chemical composition, and pharmacological properties - Wang, Jian; Sun, Mengjie; Yu, Jian; Wang, Jinglong; Cui, Qinghua (Frontiers in Pharmacology, 2024)
Pomegranate seeds (PS) are the dried seeds derived from pomegranate fruit, accounting for approximately 20% of the fruit's total weight, and are a by-product of pomegranate juice extraction.These seeds hold significance in traditional medicine among Uyghurs and Tibetan cultures, featuring diverse clinical applications within traditional Chinese medicine. These applications include management of gastric coldness and acidity, abdominal distension, liver and gallbladder fever, and pediatric enteritis. PS demonstrates properties such as stomach tonicity, qi regulation, analgesia, and anti-inflammatory effects. Extensive research underscores the richness of PS in various phytochemical compounds and metabolites, notably unsaturated fatty acids (particularly linolenic acid and linoleic acid), phenolic compounds tocopherols, proteins, and volatile oils. Notably, among these bioactive compounds, punicic acid (PA), found within PS, demonstrates potential in the prevention and treatment of cancers, diabetes, obesity, and other ailments. Despite extensive literature on pomegranate as a botanical entity, a comprehensive review focusing specifically on the chemical composition and pharmacological effects of PS remains elusive. Therefore, this review aimed to consolidate knowledge regarding the medicinal properties of PS, summarizing its chemical composition, traditional uses, and pharmacological effects in treating various diseases, thereby laying a foundation for the advancement and application of PS in the field of pharmacology.